JOSEPH CONRAD’S HEART OF DARKNESS: READER-RESPONSE THEORY - Najm Abdullah, Omar Najm Abdullah; Abdul Kareem, Danear Jabbar; Khalaf Salih, Ismail (International Journal of Psychosocial Rehabilitation, 2024)
The study is intended to prove that Heart of Darkness of Joseph Conrad can be studied from different perspectives according to the theory of reader-response. The text of the novel is probably considered thematic evidence, as it is called by Stanley Fish, in which the characters are considered to be the representative of the readers within the context itself. Moreover, Conrad’s literary work is a transactional, since the meaning of the text is expressed and conveyed essentially throughout the mutual collaboration between the reader and the text of the novel. Furthermore, the current study reflects that Conrad’s novel offers limitless space for the reader just to make him participate in the creation of its meaning basically by melting his own experience with that of the novel.